2017
DOI: 10.14814/phy2.13302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term mild hypercapnia during head‐down tilt on intracranial pressure and ocular structures in healthy human subjects

Abstract: Many astronauts experience ocular structural and functional changes during long‐duration spaceflight, including choroidal folds, optic disc edema, globe flattening, optic nerve sheath diameter (ONSD) distension, retinal nerve fiber layer thickening, and decreased visual acuity. The leading hypothesis suggests that weightlessness‐induced cephalad fluid shifts increase intracranial pressure (ICP), which contributes to the ocular structural changes, but elevated ambient CO 2 levels on the International Space Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 62 publications
9
61
1
Order By: Relevance
“…Whereas Laurie et al. (2017) observed a significant effect of CO 2 during resting conditions (supine 6° HDT), we did not (prone 6° HDT). Rather, we observed the hypercapnic augmentation of IOP during the static exercise.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whereas Laurie et al. (2017) observed a significant effect of CO 2 during resting conditions (supine 6° HDT), we did not (prone 6° HDT). Rather, we observed the hypercapnic augmentation of IOP during the static exercise.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results confirm the findings of Laurie et al. (2017) of an elevation in resting IOP during supine 6° HDT. However, in the present study, the prone 6° HDT elevated IOP much more than was observed in the supine position.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS. [73][74][75][76][77][78][79][80][81][82] These countermeasures include metabolic and pharmacologic treatments 69,[83][84][85][86][87] in the one carbon pathways; 63,69 lower body negative pressure; [74][75][76] and swim goggles to affect the translaminar pressure gradient. While current data does not seem to support prolonged, significant elevations of ICP to the levels seen in IIH, throughout LDSF, Lawley et al proposed that even mild elevations of ICP for a prolonged duration may contribute to the structural changes seen in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…Table 3 outlines some of the proposed areas for continued research in SANS. 60,78 CONCLUSION In summary, novel and unique neuro-ophthalmic findings have been documented in astronauts during and after LDSF and have been termed SANS. Although a single unifying and overreaching mechanism has yet to be proven, 1,2,[4][5][6][7][8][9]19,40,41,44,[55][56][57] and a multifactorial pathogenesis may be involved, it is likely that SANS may be the end result of cephalad fluid shifts to the brain and orbit brought about by extended MG exposure.…”
Section: Oct and Sansmentioning
confidence: 99%
“…11,12 However, as the role of ICP remains unclear, the syndrome has since been renamed spaceflight-associated neuro-ocular syndrome. 13,14 Because optic nerve pathology could result in irreversible vision loss, it has been a concern for long-duration missions (eg, 6-month International Space Station missions). The clinical standard for assessing disc edema has been the modified Frisén grading system, either quantified from dilated indirect evaluation or fundus photography of the optic nerve head (ONH).…”
mentioning
confidence: 99%